Lipid level evalution in industrialized and handmade Minas Frescal cheese and ricottas from the region of Botucatu/SP - D. Cruz, Cristina (2001)
This present work aims to evaluate the level of lipids out of the total of mass, within 12 different Minas Frescal industrialized brands and 10 varieties of Ricotta from the region of Botucatu/ SP. Information included on the packages of each product were compared with the results in order to know whether the consumer is being well informed or not. The Gerber method was used to evaluate the lipids. Results were submmited to statistical analysis using the “F Test of Variance Analysis” and Tukey test. Industrialized varieties of Minas Frescal cheese showed, in 7 out of the 12 brands, a lipid level (%) fitting the established average standard, however, none of them matched the information described in their respective packages (16%-18%). Among the handwork cheeses, 5 out of 9, matched the established standard for Minas Frescal cheeses. The ricottas, all the 10 brands analyzed here did not match the established average standard of lipids grade (%). Face to the obtained results, it’s up to the population to demand a more effective control of the imdustrialized Brazilian production.